A quantitative approach for trap analysis between Al0.25Ga0.75N and GaN in high electron mobility transistors - Walid Amir (Nature Portfolio, 2021)
Abstract The characteristics of traps between the Al0.25Ga0.75N barrier and the GaN channel layer in a high-electron-mobility-transistors (HEMTs) were investigated. The interface traps at the Al0.25Ga0.75N/GaN interface as well as the border traps were experimentally analyzed because the Al0.25Ga0.75N barrier layer functions as a dielectric owing to its high dielectric constant. The interface trap density D it and border trap density N bt were extracted from a long-channel field-effect transistor (FET), conventionally known as a FATFET structure, via frequency-dependent capacitance–voltage (C–V) and conductance–voltage (G–V) measurements. The minimum D it value extracted by the conventional conductance method was 2.5 × 1012 cm−2·eV−1, which agreed well with the actual transistor subthreshold swing of around 142 mV·dec−1. The border trap density N bt was also extracted from the frequency-dependent C–V characteristics using the distributed circuit model, and the extracted value was 1.5 × 1019 cm−3·eV−1. Low-frequency (1/f) noise measurement provided a clearer picture of the trapping–detrapping phenomena in the Al0.25Ga0.75N layer. The value of the border trap density extracted using the carrier-number-fluctuation (CNF) model was 1.3 × 1019 cm−3·eV−1, which is of a similar level to the extracted value from the distributed circuit model.